HUBUNGAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR MAHASISWA ANGKATAN 2014 PROGRAM STUDI PENDIDIKAN SENI RUPA FAKULTAS BAHASA DAN SENI UNIVERSITAS NEGERI PADANG - ANWAR FAUZI, Dra. Zubaidah, M.Pd., Drs. Yusron Wikarya, M.Pd. (Serupa The Journal of Art Education, 2018)
This purpose this study were (1) describe the relationship between learning motivation on learning achievement among student year 2014th at Majoring Applied Art of Education (2) analysis the correlation between learning motivation on learning achievement. The primary source of data were shared motivation draft to student year 2014th and data IPK got from UPT-PTIK UNP. The data collected by documentation with describtive analyze and correlation analysis technique. The eksperiment was showed is (1) learning motivation of student year 2014th at Majoring Applied Art of Education is low, there is about 29 with percentage 54,71% from 53 students. (2) the have of positive relationship among learning motivation on learning achievement, were as much as 0,430 that was included the medium category.Kata Kunci: Motivasi Belajar, Prestasi Belajar